A review of the Barbatula loaches (Teleostei: Nemacheilidae) from north-eastern China, with the description of four new species - Chen, Hao; Zhang, Hui; Chen, Yongxia; Freyhof, Jörg (Zootaxa, 2019)
The species of the genus Barbatula from north-eastern China are reviewed, based on morphological and molecular characters. A total of ten species are recognized. Barbatula nuda, B. toni, B. gibba, B. potaninorum, B. kirinensis and B. pechiliensis are treated as valid and four new species are described herein. Barbatula zhangwuensis, new species, from northern China, is distinguished by having widely spaced nostrils, a pointed snout, a shallow median incision in the upper lip, a short lateral expansion of the lower lip, the pelvic-fin origin situated behind the vertical through the dorsal-fin origin, and no scales on the back and the flank anterior to the vertical through the dorsal-fin origin and irregularly set scales on the post-dorsal back and flank. Barbatula liaoyangensis, new species, from the Taizi River (a tributary of the Liao River), is distinguished by having widely spaced nostrils, a blade-shaped lateral expansion of the mental lobe, a shallow median incision in the upper lip, a short lateral expansion of the lower lip and sparsely set scales on the back and the flank anterior to the vertical through the dorsal-fin origin, but densely set behind. Barbatula emuensis, new species, from the Heilongjiang and Yalu River drainages, is distinguished by having closely set nostrils, a deep median incision in the upper lip, no lateral expansion of the lower lip, and sparsely set scales on the back and the flank anterior to the vertical through the dorsal-fin origin, but densely set behind. Barbatula linjiangensis, new species, from the Yalu River, is distinguished by having closely set nostrils, a shallow median incision in the upper lip, no lateral expansion of the lower lip, and sparsely set scales on the back and the flank anterior to the vertical through the dorsal-fin origin, but densely set behind.